Rise of Haemoglobin after Blood Transfusion in Children Without Active Bleeding - Shrestha, Rupesh; Basnet, Srijana; Gami, Fakir Chandra (Journal of Nepal Paediatric Society, 2020)
Introduction: Blood transfusion is a common practice among children with severe anaemia. A common assumption among physician is that transfusion of 5 ml/kg packed red cell will increase the haemoglobin of the recipient by 1 gm/dl. This study was aimed at assessing the effect of volume of blood product and hematocrit of donor blood in the rise of haemoglobin concentration after transfusion in children without active bleeding. Methods: A prospective observational study was conducted in 32 children aged between one to 15 years without active bleeding who received blood transfusion in Paediatric ward and Paediatric Intensive Care Unit of a tertiary care hospital in Nepal from December 2013 to November 2014. Haemoglobin levels before and after transfusion were compared and any adverse reactions that occurred during transfusion were recorded. Hematocrit of each donor blood was measured. Results: The overall rise of haemoglobin after transfusion of blood product with hematocrit of 53 ± 8.9 % at the rate 14.5 ± 6.0 ml/kg was 2.7 ± 1.4 gm/dl. The rise of haemoglobin after transfusion of whole blood with hematocrit of 38.8 ± 4.4% at the rate 15.5 ± 6.9 ml/kg was 1.8 ± 1.2 gm/dl. The rise of haemoglobin after transfusion of packed cell with hematocrit 57.0 ± 4.8 % at the rate 14.2 ± 5.8 ml/kg was 2.9 ± 1.4 gm/dl. Conclusion: This study supports the general consensus of 1 gm/dl rise of haemoglobin after transfusion of packed red cell at 5 ml/kg.